2014
DOI: 10.1037/a0033683
|View full text |Cite
|
Sign up to set email alerts
|

Results from the multisite implementation of STAR-VA: A multicomponent psychosocial intervention for managing challenging dementia-related behaviors of veterans.

Abstract: Dementia is often associated with challenging behaviors that can significantly impact the quality of life of individuals with dementia and pose great difficulty for long-term care staff. Antipsychotic medications, historically the mainstay approach for managing such behaviors, have increasingly been associated with limited efficacy and increased death risk with older dementia patients. In an effort to promote and realize the promise of nonpharmacological management of challenging dementia-related behaviors, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…Karlin et al [41] evaluated a behavioral intervention developed by the U.S. Department of Veteran Affairs health care system for veterans with dementia titled STAR-VA. The intervention had the following three primary components:…”
Section: Staff Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Karlin et al [41] evaluated a behavioral intervention developed by the U.S. Department of Veteran Affairs health care system for veterans with dementia titled STAR-VA. The intervention had the following three primary components:…”
Section: Staff Interventionsmentioning
confidence: 99%
“…[14,[49][50][51] More recently, three staff intervention studies found significant reductions in aggression. [39][40][41] These programs tend to involve multiple sessions and teach specific skills such as identifying and modifying environmental precipitants of aggression, communication techniques, learning to view problem behaviors as an expression of an unmet need, learning to examine antecedents to aggressive behaviors and their consequences, and distraction. One important feature of some training programs evaluated is that there was an emphasis placed on individualizing intervention strategies based on a "menu" of more general strategies.…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence points out that the complex and multifaceted issues of identifying and providing care for patients with dementia in primary care are effectively addressed by comprehensive and coordinated care approaches. 19 Some of the key elements for these comprehensive care models identified are the use of multidisciplinary teams of clinicians working closely with care coordinators, social workers, and community services; these elements are also part of patient-centered medical homes. As more practices transform into patient-centered medical homes, these services may be more widely available for caring for patients with dementia.…”
mentioning
confidence: 99%
“…Recent work has translated the Staff Training in Assisted-Living Residences (STAR) program to nonresearch settings [15,16], and this program provides a set of theoretically consistent, evidence-based behavioral interventions that can be used to guide implementation efforts. There are several core features of effective behavioral intervention programs for NPS: they teach caregivers about the nature of the brain damage that occurs in dementia, so that caregivers develop more realistic expectations of the abilities of the person with dementia; they use a systematic approach to understanding NPS triggers and measuring responses to interventions in order to reduce the frequency and severity of behavioral symptoms; they teach caregivers to alter their interactions with the person with dementia to avoid NPS triggers; they advocate controlling the environment of care to avoid both overstimulation and understimulation of the patient; they capitalize on the preserved abilities of patients to form rudimentary motor or stimulus-response memories of pleasant daily events; and they use an individualized, person-centered, systematic approach to problem solving that includes evaluation of the patient's response over time and adjustment of the plan based on the patient's response.…”
mentioning
confidence: 99%